Handbook of molded part shrinkage and warpage - Fischer, Jerry M. (PDL handbook series., 2013)
How easy life would be if only moldings were the same size and shape as the mold. But they never are, as molders, toolmakers, designers and end users know only too well. Shrinkage means that the size is always different; warpage often changes the shape too. The effects are worse for some plastics than others. Why is that? What can you do about it? The Handbook of Molded Part Shrinkage and Warpage is the first and only book to deal specifically with this fundamental problem. Jerry Fischer's Handbook explains in plain terms why moldings shrink and warp, shows how additives and reinforcements change the picture, sets out the effect of molding process conditions, and explains why you never can have a single 'correct' shrinkage value. It goes on to demonstrate how to alleviate the problem through careful design of the molded part and the mold, and by proper material selection. It also examines computer-aided methods of forecasting shrinkage and warpage. And most important of all, the Handbook gives you the data you need to work with. . Authoritative and rooted in extensive industrial experience, the expert guidance contained in this handbook offers practical understanding to novices, and new insights to readers already skilled in the art of injection molding and mold making.Contains the answers to common problems and detailed advice on how to control mold and post-mold shrinkage and warpage.Case Studies illustrate and enrich the text; Data tables provide the empirical data that is essential for success, but hard to come by.